Impact of diverse musical genres on blood-feeding and mating behavior in Aedes aegypti mosquitoes - Chew Yan Ni; Nur Faeza Abu Kassim; Noor Moukhni Ayub; Sara Abdelrahman Abuelmaali; Abadi M. Mashlawi; Hamady Dieng (Journal of Vector Borne Diseases, 2025)
Background & objectives: Sound plays an important role in mosquito foraging and sexual interactions. Mosquitoes utilize acoustic signals for host location, sexual recognition, and mating, which is achieved through the rhythmic beating of their wings to generate distinct sounds characterized by specific flight tone frequencies. Methods: In this study, electronic music (Tremor by Dimitri Vegas, Martin Garrix and Like Mike) and country music (Country Road by John Denver) were played in high and low volumes to investigate the influence of different genres of music on the blood feeding and mating responses of Aedes aegypti. The observations encompassed monitoring the landing attempts, blood-feeding endeavors, and mating behavior of Ae. aegypti. Results: High-volume electronic and country music with elevated pitch and amplitude significantly reduced host attacks and blood-feeding attempts by female mosquitoes compared to low-volume or music-off conditions. Interpretation & conclusion: However, significant reduction of successful copula was only observed in Ae. aegypti mosquitoes exposed under electronic music with high volume. As transmission of dengue is through blood feeding and mating, this discovery may open new possibilities for developing music-based control strategies against mosquito-borne diseases.